Diffusion of New Products: Empirical Generalizations and Managerial Uses - Mahajan, Vijay; Muller, Eitan; Bass, Frank M. (Marketing Science, 1995)
The diffusion model developed by Bass (Bass, F. M. 1969. A new product growth model for consumer durables. Management Sci. 15(January) 215–227.) constitutes an empirical generalization. It represents a pattern or regularity that has been shown to repeat over many new products and services in many countries and over a variety circumstances. Numerous and various applications of the model have lead to further generalizations. Modifications and extensions of the model have lead to further generalizations. In addition to the empirical generalizations that stem from the model, we discuss here some of the managerial applications of the model.